Applying a hydrogeomorphic channel classification to understand spatial patterns in riparian vegetation. (25th May 2018) - Shaw, Jeremy R.; Cooper, David J.; Sutfin, Nicholas A.
Abstract: Questions: Hydrogeomorphic channel classifications are widely employed to understand natural phenomena in Earth sciences, but are rarely used in riparian vegetation studies. However, when these types of classifications correspond to physical process domains (discrete landscape units with consistent abiotic attributes), they may be useful in distinguishing habitat and vegetation types. We assessed the ecological significance of a hydrogeomorphic stream channel classification by addressing the following questions: (1) does perennial plant community composition differ among hydrogeomorphic channel types; (2) which species and functional groups contribute to compositional variation among channel types in the Sonoran Desert; and (3) what are the stream reach‐scale geomorphic drivers of compositional variation? Location: Sonoran Desert, Arizona, USA. Methods: We compared perennial riparian plant community composition among five a priori hydrogeomorphic channel types at 86 stream reaches in arid ephemeral watersheds. Floristic differences among channel types were assessed using PERMANOVA. GLM were used to identify species and functional groups whose abundance differed among channel types. Abiotic drivers of compositional differences were identified through correlations among biotic and abiotic matrices. Results: Community composition differed significantly among channel types, with distinctive vegetation in bedrock, piedmont headwater and braided channels. While different from other channel types, vegetation in bedrock with alluvium and incised alluvium channels was broadly similar, but could be distinguished by the abundance of common species and functional groups. The density of drought‐deciduous subshrubs, as well as large woody plants with evergreen, drought‐deciduous and photosynthetic stem phenology contributed to the observed compositional variance. Bed slope was the primary driver of compositional differences among channel types, with elevation providing additional explanatory power. Conclusions: Hydrogeomorphic channel classifications corresponding to distinctive fluvial process domains are useful for understanding spatial variability in riparian habitats and resulting differences in plant community composition in the Sonoran Desert. Analogous spatial patterns of riparian plant communities previously reported from other arid regions suggest that these general channel types are broadly applicable. Abstract : Hydrogeomorphic channel types corresponding to different fluvial process domains support distinctive riparian plant communities in ephemeral streams of the Sonoran Desert, USA. Compositional differences among channel types are strongly related to channel bed slope. These channel types clarify and provide context to analogous riparian vegetation patterns reported from other arid regions around the world.